Parasites Inventory in Freshwater and Seawater fish at Fish Quarantine Center and Quality Control of Fisheries Product in Surabaya II - Alvin Avia; M.F. Ulkhaq (Journal of Aquaculture Science, 2019)
One disease that often attacts fish is a group of parasites or parasitic diseases, parasites are not only dangerous because they are related to their activities, but also trigger the emergence of other pathogenic organisms and cause infections. Therefore, it is necessary to take fish quarantine measures to prevent the spread of diseases carried out by fish quarantine centers. This study was conducted to determine the type of parasite that infested fish samples and determine the prevalence and intensity of fish samples. A total of 48 sample fish consisting of freshwater and seawater fish were analyzed in the laboratory of Balai Karantina Ikan, Pengendalian Mutu dan Keamanan Hasil Perikanan Surabaya II during December - January 2019, either directly or directly (ectoparasites and endoparasites). Parasitic identification was carried out visually and microscopically with an approach based on identification books. The types of parasites that we found during the study consisted of Argulus sp, Trichodina sp, Anisakis sp., Gnathostoma spinigerum, and Gnathostoma spinigerum. The highest prevalence in Scomber Scombrus with Anisakis sp. Amounting  to 77.8%, mean while, the lowest prevalence and the intensity is found in Thunnus sp. The prevalence and intensity of parasites are influenced by water quality and pollution.